REVIEW OF MINIMUM AGE REQUIREMENT FOR IN-FLIGHT PASSENGERS - Suwinto Johan (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The issue related to passenger age requirement on airplanes has emerged as a significant concern. There have been numerous instances of young passengers boarding incorrect flights, highlighting the critical need for attention. Additionally, the potential risk of aircraft accidents poses a grave danger to children onboard. The criteria and regulations surrounding minimum passenger age requirements vary widely. This study focuses on the necessity of establishing a minimum age for airline passengers and the criteria for determining passenger age in alignment with legal standards. This normative juridical research reviewed and analyzed the regulations concerning minimum age requirements and age policies adopted by airline companies. The result showed that minimum age requirement for passenger differs across various legal systems and policies implemented by countries and airlines.